ASYMMETRIC ALDOL AND ALKYLATION REACTIONS MEDIATED BY THE QUAT CHIRAL AUXILIARY (R)-(-)-5-METHYL-3,3-DIMETHYL-2-PYRROLIDINONE - Davies, S; Doisneau, G; Prodger, J; Sanganee, H (1994)
Enolates derived from the N-propionoyl derivative of the "quat" chiral auxiliary (R)-(-)-5-methyl-3,3-dimethyl-2-pyrrolidinone undergo highly stereoselective aldol and alkylation reactions. Removal of the auxiliary has been demonstrated with LiOH, PhCH2OLi, MeOMgBr and LiAlH4 to generate respectively (2R,3R)-3-hydroxy-2-methyl-3-phenylpropionic acid in homochiral form, and with 96% e.e. (S)-2-methyl-3-phenylpropionic acid and derived methyl and benzyl esters and with >94% e.e. (S)-2-methyl-3-phenylpropanol. © 1994.